2014
DOI: 10.26537/iirh.v0i2.2029
|View full text |Cite
|
Sign up to set email alerts
|

Por que investem as empresas na formação contínua?

Abstract: A importância da formação contínua é objeto de um consenso generalizado quer junto da comunidade científica quer dos responsáveis pela sua implementação nos mais variados contextos organizacionais. Todavia, em torno deste consenso, constroem-se significações e práticas radicalmente distintas que nos propomos analisar nesta comunicação. Assim, num primeiro momento pretendemos dar conta das diferentes configurações semânticas que a importância atribuída à formação profissional assume. Para tal, analisamos o pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They believe that one of the key barriers to academic staff taking a proactive role in making the social contribution is associated with the academic reward and evaluation system, the so called, Research Assessment Exercise (RAE). The number of publications and teaching time are still considered as the most important academic criteria directly related to the promotion and evaluation of researchers in universities in the U. K. This relates to research by Alves (1998) who observed that in some cases the academic researchers were more inclined towards the fulfilment of their research interests and scientific curiosity than towards complying with the deadlines they agreed with their industrial partners. Feller (1990) has advanced the argument that the efforts to foster `privatisation of research' may actually slow down the rate of technological innovation.…”
Section: Barriers To the Development Of Entrepreneurial Universitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They believe that one of the key barriers to academic staff taking a proactive role in making the social contribution is associated with the academic reward and evaluation system, the so called, Research Assessment Exercise (RAE). The number of publications and teaching time are still considered as the most important academic criteria directly related to the promotion and evaluation of researchers in universities in the U. K. This relates to research by Alves (1998) who observed that in some cases the academic researchers were more inclined towards the fulfilment of their research interests and scientific curiosity than towards complying with the deadlines they agreed with their industrial partners. Feller (1990) has advanced the argument that the efforts to foster `privatisation of research' may actually slow down the rate of technological innovation.…”
Section: Barriers To the Development Of Entrepreneurial Universitiesmentioning
confidence: 99%
“…Meanwhile universities gained benefits in their cooperation with industry by adding financial resources, new technical knowledge and good practices; access to industrial information and applied knowledge that can be employed for academic research and teaching (Martin, 2000). Alves (1998) and Nieminen and Kaukonen (2001) Etzkowitz and Leydesdorff (1997) that the university -industry relationship emerges as a sophisticated instrument for the reinforcement of firms' competitive position through adoption of advanced, innovative and value-added technologies. The next section explores research which suggests the different factors that explain how in spite of wide recognition that relationships between academia and industry are mutually beneficial, the levels of interaction remain very low.…”
Section: Perceived Benefits Of Industry and Government Collaborationmentioning
confidence: 99%